Addressing sustainable rural development with shared value: a Peruvian model from the cacao industry - Borda, Armando (2021)
Here we present a model aimed at contributing to the literature around sustainable supply chains by examining a novel redesign initiative of the chocolate supply chain within the Peruvian cacao (cocoa) industry. Using the Creating Shared Value (CSV) framework, we apply the case study method in examining the Peruvian Cacao Alliance’s experience in redesigning both the stages and relationships within its supply of cacao to the world. Data were collected from both primary and secondary sources and analyzed after coding from categories defined in the literature on CSV. The case demonstrates the opportunity to successfully participate in the supply chains of globally recognized, consumer-facing chocolate brands while simultaneously obtaining social, economic and environmental benefits for the rural communities that supply cacao. While addressing both social and business gains remains fairly important for supply chain members, there are several implementation challenges that need to be considered to achieve the goals of CSV strategies in a sustained way. By analyzing the experience of this particular cacao value chain, we are able to offer practical insight on how to more effectively implement the creating shared value approach, thereby illuminating that it is possible for value generated through such supply chains to be more equitably shared. As such, we provide a valuable initial step in better understanding how the CSV concept applies in practice by identifying its boundary conditions for achieving improved cacao supply chain practices and relationships.